Systematic Literature Review: The Implementation of Case-Based Learning (CBL) In Chemistry Education - Evelyn Azizah Anindya Puteri; Munzil; Sumari (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This study aims to analyze research trends, variations in the application of syntax, as well as the effectiveness and limitations of Case-Based Learning (CBL) in chemistry education. The method used is a Systematic Literature Review (SLR) guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Of the 30 articles selected, 17 met the criteria and were analyzed further. The articles analyzed were published in the period 2010–2025. The reviewed articles show that the implementation of CBL has developed since 2010, with the highest number of publications in Turkey and samples predominantly at the university level. The topics covered vary, including reaction rates, solution equilibrium, acids and bases, and green chemistry. The commonly used syntax includes case orientation, analysis and discussion, literature review, presentation of results, and concept clarification. In general, CBL has been proven to improve cognitive aspects (concept understanding, achievement, retention) and process aspects (motivation, attitude, and critical thinking skills). However, CBL also has limitations, such as small sample sizes, lack of integration of modern chemistry topics, limited implementation at the high school level, and the time consuming nature of its application.